8 Things Super-Performers have in Common - Paetyangkul, Sirinart (Journal of Multidisciplinary in Social Sciences, 2023)
Following someone’s page on Facebook has become one of the common things we do, and this author is one several I have been following; Mr.Parin Songpracha. He has been sharing his experiences and updating his fans with new trends and custom in business practice. The 8 Things Super-Performers have in Common is composed for several year from his success and failure experience from the beginning of his career . Over 400 of his writing and share on his fan page, only 64 topics which each has over 100 shares, are selected to be in this book. Personal impression of this book is a mixture of tips and tricks, storytelling of someone who has been through tough times until succeeded and would like to share do’s and don’ts. The book is easy to digest and practical. Anyone who works in organization or when individuals deal with people, this could be useful to reference as guidelines. There is no need to start reading chapter by chapter, it can be read from topic interested. The first jobbers, as well, could benefit from reading several chapters since the junior has fewer years of service. The book is like personal mentor!